On the Confessions as confessio: a reader's guide - David, Barry (Reading Augustine, 2022)
"This is a new guide to reading the Confessions, Augustine's most important work. It is widely known as the first Western Christian autobiography ever written, the great masterpiece of Western literature. The Confessions consists of 13 books, in which Augustine outlines his sinful youth and his conversion of Christianity. Barry David guides the reader swiftly through this convoluted texts, explaining the historical context, as well as the various philosophical concepts; and considers its spiritual, ecclesial and theological significance. As with other titles in the Reading Augustine series, this book presents concise introductory reading of Augustine's work from one of the leading scholar in the field."--